Association of Pre-Operative Islamic Assistance with Anxiety Reduction Among Surgical Patients: A Pre-Experimental Study - Nova Maryani; Miftahulhaq; Ardi Pramono; Yosy Budi Setiawan; Hana Maliha Ruhaini; Winny Setyonugroho; Muhammad Arif Rizqi (Indonesian Journal of Anesthesiology and Reanimation, 2026)
Introduction: Preoperative anxiety is a common psychological response among patients undergoing elective surgery and may contribute to adverse physiological and psychological outcomes. Spiritual care has been increasingly explored as a complementary non-pharmacological approach to support patients before surgery. Objective: To examine the association between pre-operative Islamic assistance and changes in anxiety levels among patients undergoing elective surgery. Methods: A quantitative pre-experimental study using a one-group pretest–posttest design was conducted among 56 adult patients undergoing elective surgery who were recruited using purposive sampling. Participants received a structured pre-operative Islamic assistance session consisting of spiritual education, prayer guidance, and dzikr. Anxiety levels were measured before and after the intervention using the Hamilton Anxiety Rating Scale (HARS). Data were analyzed using a paired-sample t-test at a 95% confidence level. Results: Anxiety scores significantly decreased following the intervention (mean difference=1.05, SD=0.22, t(55)=34.7, p<0.001; 95% CI: 0.99–1.11). Lower anxiety scores were observed after the intervention; however, because no control group was included, these findings should be interpreted as an association rather than evidence of a causal effect. Conclusion: Structured pre-operative Islamic assistance may be associated with reduced anxiety among patients undergoing elective surgery. Randomized controlled trials with larger samples are warranted to confirm these findings before broader implementation.